Influence of Microsprinkler Irrigation Amount on Water, Soil, and pH Profiles in a Coastal Saline Soil - Linlin Chu; Yaohu Kang; Shuqin Wan (The Scientific World Journal)
Microsprinkler irrigation is a potential method to alleviate soil salinization. After conducting a homogeneous, highly saline, clayey, and coastal soil from the Bohai Gulf in northern China in a column experiment, the results show that the depth of the wetting front increased as the water amount applied increased, low-salinity and low-SAR enlarged after irrigation and water redistribution, and the soil pH increased with an increase in irrigation amount. We concluded that a water amount of 207 mm could be used to reclaim the coastal saline soil in northern China.